2007
DOI: 10.1111/j.1464-5491.2007.02079.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized controlled study of Hydrofiber® dressing containing ionic silver or calcium alginate dressings in non‐ischaemic diabetic foot ulcers

Abstract: When added to standard care with appropriate off-loading, AQAg silver dressings were associated with favourable clinical outcomes compared with CA dressings, specifically in ulcer depth reduction and in infected ulcers requiring antibiotic treatment. This study reports the first significant clinical effects of a primary wound dressing containing silver on DFU healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
90
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(93 citation statements)
references
References 27 publications
0
90
0
3
Order By: Relevance
“…Pooling the three hydrogel RCTs suggested that hydrogels are significantly more effective than gauze or standard care in healing diabetic foot ulcers [8]. Adding silver into the dressing also demonstrated to be extra efficacious [9]. Surgical debridement [23] and larval therapy [21] showed no significant benefit [8].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pooling the three hydrogel RCTs suggested that hydrogels are significantly more effective than gauze or standard care in healing diabetic foot ulcers [8]. Adding silver into the dressing also demonstrated to be extra efficacious [9]. Surgical debridement [23] and larval therapy [21] showed no significant benefit [8].…”
Section: Resultsmentioning
confidence: 99%
“…Pooling the three hydrogel RCTs suggested that hydrogels are significantly more effective than gauze or standard care in healing diabetic foot ulcers [8]. Recently, a trial with hydro-fibres with added ionic silver demonstrated a better clinical outcome for ulcers treated with dressings containing silver [9].…”
Section: Autolytic Debridementmentioning
confidence: 99%
“…We therefore focused our analyses on the proportion of ulcers healed (or risk of healing). In terms of ulcer severity, four studies 263,268,269,273 reported the inclusion of people with Wagner grade 1 or 2 ulcers and one study 264 specified that ulcers were superficial. A further three studies specified that people with ulcers involving tendons, joint spaces and/or bone were excluded.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…[261][262][263][264][265][266][267][268][269][270][271][272][273][274][275] A Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flowchart is presented in Appendix 12 and a summary of study characteristics for the included studies is presented in Table 65. All 15 included studies reported the number of ulcers healed, whereas only three 262,264,266 reported median time to healing.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation